Vaccination with Bivalent DNA Vaccine of α1-Giardin and CWP2 Delivered by Attenuated Salmonella typhimurium Reduces Trophozoites and Cysts in the Feces of Mice Infected with Giardia lamblia. - Xian-Min Feng (PLoS ONE, 2016)
BACKGROUND:Giardia lamblia is one of the most common infectious protozoans in human that may cause diarrhea in travelers. Searching for antigens that induced effectively protective immunity has become a key point in the development of vaccine against giardiasis. METHODOLOGY/PRINCIPAL FINDINGS:Mice vaccinated with G. lamblia trophozozite-specific α1-giardin DNA vaccine delivered orally by attenuated Salmonella typhimurium SL7027 elicited 74.2% trophozoite reduction, but only 28% reduction in cyst shedding compared with PBS buffer control. Oral vaccination with Salmonella-delivered cyst-specific CWP2 DNA produced 89% reduction in cysts shedding in feces of vaccinated mice. Significantly, the mice vaccinated with Salmonella-delivered bivalent α1-giardin and CWP2 DNA vaccines produced significant reduction in both trophozoite (79%) and cyst (93%) in feces of vaccinated mice. This parasite reduction is associated with the strong local mucosal IgA secretion and the IgG2a-dominant systemic immune responses in vaccinated mice. CONCLUSIONS:The results demonstrate that bivalent vaccines targeting α1-giardin and CWP2 can protect mice against the colonization of Giardia trophozoite and block the transformation of cyst in host at the same time, and can be used to prevent Giardia infection and block the transmission of giardiasis.